2014
DOI: 10.1152/ajplung.00200.2014
|View full text |Cite
|
Sign up to set email alerts
|

The genome-wide transcriptional response to neonatal hyperoxia identifies Ahr as a key regulator

Abstract: Premature infants requiring supplemental oxygen are at increased risk for developing bronchopulmonary dysplasia (BPD). Rodent models involving neonatal exposure to excessive oxygen concentrations (hyperoxia) have helped to identify mechanisms of BPD-associated pathology. Genome-wide assessments of the effects of hyperoxia in neonatal mouse lungs could identify novel BPD-related genes and pathways. Newborn C57BL/6 mice were exposed to 100% oxygen for 10 days, and whole lung tissue RNA was used for high-throughp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

9
36
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 39 publications
(45 citation statements)
references
References 35 publications
9
36
0
Order By: Relevance
“…ceRNA) regulatory network map analysis is the discovery of miRNAs that bind to both circRNA and mRNA, and the TGF‐β and p53 pathways with which circRNA is associated. Previous studies report that hypoxia‐inducible factor 1‐alpha and CCND1 are involved in the progression of BPD . The network map we created is consistent with these studies and the circRNAs that are involved may regulate the development and progress of BPD through the predicted networks.…”
Section: Discussionsupporting
confidence: 83%
“…ceRNA) regulatory network map analysis is the discovery of miRNAs that bind to both circRNA and mRNA, and the TGF‐β and p53 pathways with which circRNA is associated. Previous studies report that hypoxia‐inducible factor 1‐alpha and CCND1 are involved in the progression of BPD . The network map we created is consistent with these studies and the circRNAs that are involved may regulate the development and progress of BPD through the predicted networks.…”
Section: Discussionsupporting
confidence: 83%
“…These data highlight the ability of induction agents per se to alter lung development and the lung transcriptome when used to drive genome recombination. These are important considerations, given the increasing use of both conditional, inducible genome recombination (Surate Solaligue et al, ) and RNA‐Seq (Bhattacharya et al, ; Coarfa et al, ) to study post‐natal lung development. It may be useful to extend this idea to examine the inertness of other control interventions employed in newborn and adolescent mice for any impact on “baseline” alveolar architecture.…”
Section: Discussionmentioning
confidence: 99%
“…Studies on alveolarization generally rely on the identification and validation of pathways that direct lung development, using pharmacological and genetic approaches. Small‐molecule and proteinaceous modulators of developmental pathways have been administered via the enteral or parenteral routes, and subsequently, the impact on the development of the lung structure might be assessed microscopically (Valenzuela et al, ) or radiologically (Xiao et al, ); alongside screens for transcriptomic changes (Mariani, ), by microarray, or more recently, RNA‐Seq (Bhattacharya et al, ; Lingappan et al, ) technology. Small‐molecule interventions have, in the past, relied on enzyme inhibitors to block enzyme function (Reviewed in Madurga et al, ; Silva et al, ; Surate Solaligue et al, ); but have recently been expanded to include chemical chaperones (Nguyen and Uhal, ; Siddesha et al, ) and genetic interference, through sequence‐specific modulation of microRNA function using antagomiRs (Nardiello and Morty, ) or microRNA mimics (Olave et al, ; Durrani‐Kolarik et al, ).…”
mentioning
confidence: 99%
“…Using Ingenuity pathways analysis analysis tools, we identified 3 canonical pathways represented by the 21 genes present in the observed recurrent CNV regions, which included aryl hydrocarbon receptor signaling, xenobiotic metabolism signaling, and glutathionemediated detoxification. Recently, it was shown that the aryl hydrocarbon receptor signaling pathway is dysregulated in the lungs of neonatal mice exposed to hyperoxia, a treatment that results in BPD-like pathology (37). Exposure to high concentrations of supplemental oxygen generates free radicals which Articles Ahmad et al…”
Section: Discussionmentioning
confidence: 99%